2005
DOI: 10.14742/ajet.1338
|View full text |Cite
|
Sign up to set email alerts
|

Teaching IP networking fundamentals in resource constrained educational environments

Abstract: Many educational institutions suffer from a lack of funding to keep telecomm-unications laboratory classes up to date and flexible. This paper describes our Remote Unix Lab Environment (RULE), a solution for exposing students to the latest Internet based telecommunications software tools in a Unix like environment. RULE leverages existing PC laboratories (often based on Microsoft's Windows) to enable student access to Internet Protocol (IP) networked hosts for telecommunications coursework and research project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Over the past few years, hands on exercises using VMs have been tried successfully in courses related to information, web or computational security (Tao, Chen & Lin, 2010;Gephart & Kuperman, 2010;Hay, Dodge & Nance, 2008;Hickman, 2008;Bullers, Burd & Seazzu, 2006;Adams & Laverell, 2005), operating systems (Nieh & Vaill, 2005;Adams & Laverell, 2005), Windows and Linux system administration (Hickman, 2008;Stackpole et al, 2008), database (Cranitch & Rees, 2009), computer forensics (Hickman, 2008;Bullers, Burd & Seazzu, 2006), data communications (Hickman, 2008) and networking (Stackpole et al, 2008;Bullers, Burd & Seazzu, 2006;Adams & Laverell, 2005;Armitage & Harrop, 2005). Most of these publications describe case studies of the use of VMs in specific IT courses and focus on the content of the exercises and how the lessons were conducted.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, hands on exercises using VMs have been tried successfully in courses related to information, web or computational security (Tao, Chen & Lin, 2010;Gephart & Kuperman, 2010;Hay, Dodge & Nance, 2008;Hickman, 2008;Bullers, Burd & Seazzu, 2006;Adams & Laverell, 2005), operating systems (Nieh & Vaill, 2005;Adams & Laverell, 2005), Windows and Linux system administration (Hickman, 2008;Stackpole et al, 2008), database (Cranitch & Rees, 2009), computer forensics (Hickman, 2008;Bullers, Burd & Seazzu, 2006), data communications (Hickman, 2008) and networking (Stackpole et al, 2008;Bullers, Burd & Seazzu, 2006;Adams & Laverell, 2005;Armitage & Harrop, 2005). Most of these publications describe case studies of the use of VMs in specific IT courses and focus on the content of the exercises and how the lessons were conducted.…”
Section: Related Workmentioning
confidence: 99%
“…Documented examples of real implementations based on the centralised model include (i) the virtual computer lab project (Gephart, 2010), (ii) the virtual computing lab at North Carolina State University (Li, 2009), (iii) the virtual IT teaching lab at Bond University (Cranitch & Rees, 2009), (iv) the multi-course systems lab at Calvin's College (Adams & Laverell, 2005) and (v) the Remote Unix Lab Environment at Swinburne University of Technology (Armitage & Harrop, 2005). Examples of decentralised implementations can be found at Pace University (Tao & Chen, 2010), Utah Valley State College (Hickman, 2008), and the virtual network lab at the University of New Mexico (Bullers, Burd & Seazzu, 2006).…”
Section: Related Workmentioning
confidence: 99%
“…Prior research on virtual operating systems contribution to a data center's infrastructure has shown that it is certainly possible to reduce the number of physical computers required to perform the same functions. This new architecture draws less power, generates less heat, and takes up less physical space (Armitage & Harrop, 2005). Further, because fewer computers are required in the data center, additional advantages are also gained in regard to less physical maintenance and simplicity of design (Lowell, Saito, & Samberg, 2004).…”
Section: Green Computing and Virtualizationmentioning
confidence: 99%